Status Hukum Dokumen Kependudukan Aliran Kepercayaan setelah Putusan Mahkamah Konstitusi Nomor 97/PUU-XIV/2016 - Anom Penatas; Supriyadi Supriyadi; husein Muslimin; Ferry Anggriawan (Bhirawa Law Journal, 2020)
Believing communities who previously did not get the same legal status in the inclusion of religious column status in population documents such as e-KTPs and family cards are very detrimental, because they do not get equal rights with religious communities whose religion has been recognized in their life in the Unitary State Republic of Indonesia. Believers often face difficulties and discrimination in their daily lives, such as in finding work, marriage, as well asdifficulties in getting a proper funeral because the information on the religion column in the population documents is only marked with a dash (-). The Constitutional Court Decision Number 97 / PUU-XIV / 2016 greatly helps equalize the Community of Beliefs in their life in the Unitary State of the Republic of Indonesia by filling in the column Belief in God Almighty in the Religioncolumn in the population documents for Believers, with a statement of Belief that will equalize The life of a Believer of Beliefs such as getting a decent job, a marriage in accordance with their beliefs, and being able to get a proper burial place. The problem that arises is what is the legal status of population documents after the issuance of the MK decision? Considering that in thePopulation Administration Law, the Government still applies the sign (-) to adherents of belief